Inaugural Forum Tun Razak : New challenges facing rural development and poverty eradication - Inaugural Forum Tun Razak( 2005 : Kuala Lumpur, Malaysia); Nungsari Ahmad Radhi, editor (Kuala Lumpur : Lembaga Pemegang Amanah Yayasan Tun Razak, 2005)
PSZJBL